2007
DOI: 10.1097/hjh.0b013e3282775992
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring and target organ damage in pediatrics

Abstract: The prevalence of hypertension in children and adolescents is rising in association with the increasing rate of childhood obesity, and it is associated with early target organ damage. Published guidelines on high blood pressure in children and adolescents, focused on the early and accurate diagnosis of hypertension, resulted in improved ability to identify children with hypertension. Although auscultation using a mercury sphygmomanometer remains the method of choice for evaluation of hypertension in children, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 117 publications
(153 reference statements)
2
59
0
4
Order By: Relevance
“…With ABPM, BP is measured in the patient's usual environment, eliminating the white coat effect and allowing assessment of circadian variability (i.e., awake vs. sleep BP) neither of which are possible with cBP measurements. ABPM is the only technique that can detect masked hypertension (normal office BP but elevated out-of-office BP), which is associated with increased cardiovascular risk and development of target-organ damage [15,22,23]. Additionally, ABPM allows estimation of the mean BP, BP load (percentage of elevated readings) and BP variability, all of which have been shown to have important prognostic implications.…”
Section: The Potential Importance Of Ambulatory Bp Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…With ABPM, BP is measured in the patient's usual environment, eliminating the white coat effect and allowing assessment of circadian variability (i.e., awake vs. sleep BP) neither of which are possible with cBP measurements. ABPM is the only technique that can detect masked hypertension (normal office BP but elevated out-of-office BP), which is associated with increased cardiovascular risk and development of target-organ damage [15,22,23]. Additionally, ABPM allows estimation of the mean BP, BP load (percentage of elevated readings) and BP variability, all of which have been shown to have important prognostic implications.…”
Section: The Potential Importance Of Ambulatory Bp Monitoringmentioning
confidence: 99%
“…Additionally, ABPM allows estimation of the mean BP, BP load (percentage of elevated readings) and BP variability, all of which have been shown to have important prognostic implications. Abnormalities of ambulatory BP predict adverse cardiovascular events in adults such as myocardial infarction, stroke, and death [20], and also predict the development of hypertensive target-organ damage (e.g., left ventricular hypertrophy) in both adults [20] and children [11,15,22,23]. Given this, ABPM is superior to cBP for detecting the elevated cardiovascular risk associated with conditions such as obesity, diabetes, and CKD, and therefore would enable earlier implementation of interventions designed to reduce future cardiovascular disease.…”
Section: The Potential Importance Of Ambulatory Bp Monitoringmentioning
confidence: 99%
“…18 However, some studies failed to reveal an independent association of casual and/or ambulatory systolic/diastolic BP with LVMI or the presence of left ventricular hypertrophy, implying that factors such as the duration of hypertension or the characteristics of the study population (age, gender, presence of obesity or other comorbidities) may have an important role. [31][32][33] In the present study, LVM was significantly associated with systolic BP (mainly HBP and ABP and less so for CBP), nevertheless, LVMI was not significantly associated with systolic BP irrespective of the method used.…”
Section: Discussionmentioning
confidence: 99%
“…15 Reference values for ambulatory BP (ABP) in children are available 16,17 and accumulating data suggest that this method is more accurate in the diagnosis of hypertension and more closely associated with target-organ damage than the conventional clinic BP (CBP) measurements. 18 On the other hand, home BP (HBP) monitoring is regarded as an easily applicable and useful adjunct to CBP for the assessment of hypertension in adults; however data in children and adolescents are limited. 19,20 Only recently, reference HBP values in the pediatric population have been published but there is no evidence on their relationship with target-organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…5 Masked hypertension (MH) is an elevated daytime or awake ambulatory blood pressure (BP) in the presence of a normal BP on conventional measurement at the office. [5][6][7][8] Previous studies demonstrated that MH in adults is associated with left ventricular (LV) hypertrophy 5,7,8 and a worse cardiovascular prognosis. 5,[7][8][9] Successful repair of AoC is not always associated with normalisation of the BP profile, 1,3,10 even when these patients are identified as normotensive by office BP measurement.…”
mentioning
confidence: 99%